Factors Associated with Anemia in Adolescents and Its Prevention Strategies: Systematic Review - Melani, Margareta; Supriyatin, Dedeh; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Anemia is a global health issue affecting various age groups, including teenagers. This systematic review aims to identify the causes and treatments of anemia in adolescents. Using the Systematic Literature Review method, data were sourced from four databases: PubMed, Science Direct, Google Scholar, and SCOPUS. The literature search employed the keywords